CARAGEENAN OLIGOSACCHARIDES : BIOLOGICAL ACTIVITY AND ITS DEVELOPMENT OPPORTUNITIES IN INDONESIA - Subaryono, Subaryono (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Oligosaccharides from hydrocolloids especially carrageen now get a lot of attention because of the abundant raw material availability and various biological activities so it is potentially used in various fields both in the field of food and non food. Like oligosaccharides of terrestrial materials, carageenan oligosaccharides have many biological activities such as antibacterial, antiviral, antioxidant, immunomodulatory, antiinflamatory, anticancer, and other biological activity. Oligosaccharide carrageen can be produced either physically, chemically or enzymatically. This paper reviews articles on oligosaccharide carageenan, how it is produced, biological activity and development opportunities in Indonesia.